2021
DOI: 10.1159/000521665
|View full text |Cite
|
Sign up to set email alerts
|

Surgery versus Radiofrequency Ablation for Small Hepatocellular Carcinoma: A Randomized Controlled Trial (SURF Trial)

Abstract: Introduction: It remains unclear which of surgery or radiofrequency ablation (RFA) is the more effective treatment for small hepatocellular carcinoma (HCC). We aimed to compare survival between patients undergoing surgery (surgery group) and patients undergoing RFA (RFA group). Methods: We conducted a randomized controlled trial involving 49 institutions in Japan. Patients with Child-Pugh scores ≤ 7, largest HCC diameter ≤ 3 cm, and ≤ 3 HCC nodules were considered eligible. The co-primary endpoints were recurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
74
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(90 citation statements)
references
References 26 publications
(31 reference statements)
0
74
1
Order By: Relevance
“…A Japanese multicenter RCT conducted in 2021 noted no significant difference in RFS between the LR and radiofrequency ablation groups in HCCs with a diameter < 3 cm and in those with three or fewer tumors (39). In this RCT, 69 of 150 patients (46%) underwent anatomical resection, but the prognostic impact of the technique was not studied.…”
Section: Anatomic Resection Vs Non-anatomic Resectionmentioning
confidence: 84%
See 1 more Smart Citation
“…A Japanese multicenter RCT conducted in 2021 noted no significant difference in RFS between the LR and radiofrequency ablation groups in HCCs with a diameter < 3 cm and in those with three or fewer tumors (39). In this RCT, 69 of 150 patients (46%) underwent anatomical resection, but the prognostic impact of the technique was not studied.…”
Section: Anatomic Resection Vs Non-anatomic Resectionmentioning
confidence: 84%
“…If surgery cannot be delayed, other local treatments should be considered. For HCCs with a diameter < 3 cm and < 3 tumors, ablation can produce results comparable to surgery (39). For larger tumors, TACE may be considered as a bridging treatment until resection.…”
Section: Covid-19 Pandemicmentioning
confidence: 99%
“…14,15 For small cancers (multiples tumors <2 cm), resection and thermal ablation showed similar results in terms of survival, while resection was associated with a lower rate of local progression, at the cost of greater morbidity. 9,16,17 For very early HCC and in the presence of two or three nodules ⩽3 cm, Cuchetti et al showed that RFA is more cost-effective than resection; for single larger early stage HCCs, surgical resection remains the best strategy compared to monopolar RFA because of better survival rates at an acceptable increase in cost. 16 Response rates to ablation are excellent, with 5year overall survival (OS) of up to 68%.…”
Section: Ablation Versus Resection Versus Liver Transplantation?mentioning
confidence: 99%
“…[ 15 ] The researchers decided indeed to carry out a propensity score adjustment to restrict the analysis to a subgroup of comparable subjects, finally including less than half of the total surgical population. Probably, only a restricted population of patients is really identically suitable for both resection and ablation, and indeed a recently published randomized trial comparing surgery to ablation [ 14 ] had to be prematurely terminated because of insufficient recruitment of patients eligible for randomization. Ablation will likely remain offered as the reference technique to more‐fragile patients, in keeping with the multidisciplinary choices.…”
mentioning
confidence: 99%
“…Such a prospective, randomized study is likely to remain a dream rather than becoming reality, and, in fact, a recent randomized study addressed to patients with HCC <3 cm in size was prematurely concluded because of insufficient recruitment. [ 14 ] Given that, for the above reasons, a randomized study will not come early, or not at all, we must make a decision on the current evidence. We must then consider that MWA ablation provides comparable survival, but shorter RFS.…”
mentioning
confidence: 99%